2004
DOI: 10.4141/s03-018
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus fractions in soil amended with organic and inorganic phosphorus sources

Abstract: . 2004. Phosphorus fractions in soil amended with organic and inorganic phosphorus sources. Can. J. Soil Sci. 84: 83-90. Information on the P fractions in soils treated with different organic amendments is needed to better manage land application of organic amendments to agricultural soils. This study investigated the forms and distribution of P after 1, 4 and 16 wk in a Lakeland silty clay loam soil using a sequential fractionation procedure. Phosphorus was added at rates of 0, 123, 307 and 614 mg P kg -1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 17 publications
4
36
1
1
Order By: Relevance
“…In this fraction, humic and fulvic acids are the main constituents and the fulvic acids are more labile compounds and contain higher P concentrations (Ivanoff et al, 1998;Schroeder and Kovar, 2006). Finally, the residual fraction might act as P sink in systems treated with P, mainly with fertilizers or residues (Ivanoff et al, 1998;Kashem et al, 2004;Hao et al, 2008). Thus, soils fertilized with excess P, mainly as organic fertilizers, tend to accumulate non-labile P, as occurred in plots treated with manure in this work (Table 3).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In this fraction, humic and fulvic acids are the main constituents and the fulvic acids are more labile compounds and contain higher P concentrations (Ivanoff et al, 1998;Schroeder and Kovar, 2006). Finally, the residual fraction might act as P sink in systems treated with P, mainly with fertilizers or residues (Ivanoff et al, 1998;Kashem et al, 2004;Hao et al, 2008). Thus, soils fertilized with excess P, mainly as organic fertilizers, tend to accumulate non-labile P, as occurred in plots treated with manure in this work (Table 3).…”
Section: Resultsmentioning
confidence: 67%
“…In a soil incubation trial in laboratory, the application of swine manure caused an initial increase of water-soluble P concentrations, but after 16 weeks of incubation, water soluble P decreased with simultaneous increase of the P-NaHCO 3 fraction. Moreover, the application of cattle manure decreased soluble P, while other more stable P forms increased, suggesting that microorganisms transformed labile-Pi into Po, due to the higher amount of grass residues and higher C/P ratio in the manure (Kashem et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…However, STP measurements indicated that less than or equal to 120 kg ha Á1 of labile P was present in the soil. Over time, transformation of labile P into non-labile fractions occurs through soil sorption processes, and highly labile, water extractable P fractions are gradually converted into less labile NaHCO 3 and NaOH extractable inorganic P. Results from Manitoba also showed that under SCM application, microbial uptake of labile P occurred, because it contained a high straw content that promoted P immobilization (Kashem et al 2004). Soil sorption and uptake by microbial processes reduces the measurable labile P fraction, and does not provide a quantitative estimate of the total P soil loading rate.…”
Section: Dixonmentioning
confidence: 99%
“…The availability of city wastes, cow and chicken manures P to crops and its impact on soil P pool may differ from that of inorganic P fertilizer [6][7][8]. McCoy et al [8] found that biosolids (treated City wastes) P was four to seven times less available than triple super phosphate P. In contrast, other studies have suggested that P in organic amendments may be equally or more available than fertilizer P [9,10].…”
Section: Introductionmentioning
confidence: 99%